2009 1st Asia Symposium on Quality Electronic Design 2009
DOI: 10.1109/asqed.2009.5206305
|View full text |Cite
|
Sign up to set email alerts
|

Process-variation- and random-dopant-induced static noise margin fluctuation in nanoscale CMOS and FinFET SRAM cells

Abstract: In this study, a three-dimensional "atomistic" coupled device-circuit simulation approach is advanced to investigate the process-variation-effect (PVE) and random dopant fluctuation (RDF) induced characteristic fluctuations in planar metal-oxide-semiconductor field-effect-transistor (MOSFET) static random access memory (SRAM) from 65nm to 16-nm gate length. Our preliminary results show that the RDF dominates the fluctuation of static noise margin (SNM). As the gate length of the planar MOSFETs scales from 65 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Hence, for a given bit-line width, by using both (8) and (16), the existence of EM and functional failure of a generated SRAM array sample can be verified.…”
Section: Em Prevention Scheme and Trade-off Between Functional And Emmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, for a given bit-line width, by using both (8) and (16), the existence of EM and functional failure of a generated SRAM array sample can be verified.…”
Section: Em Prevention Scheme and Trade-off Between Functional And Emmentioning
confidence: 99%
“…Previous works [8][9] [10] only focused on relationships between process variation and functional failures in SRAM. Some papers considered reliability effects such as NBTI and concluded that slight performance degradation can be expected after 10 years of operation [11].…”
Section: Introductionmentioning
confidence: 99%